2008
DOI: 10.1002/cssc.200700140
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Citronellal to Citronellic Acid by Molecular Oxygen Using Supported Gold Catalysts

Abstract: The oxidation of citronellal to citronellic acid was studied using molecular oxygen as oxidant and gold-containing supported catalysts under aqueous conditions. The reactions were carried out at 60-90 degrees C, with 200 Nml min(-1) O2 and at pH values from 9 to 12. The alumina- or titania-supported catalysts were synthesized according to the deposition-precipitation procedure using urea or NaOH. Mechanistic studies have revealed that radical-initiated reactions lead to undesired by-products especially at pH <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The specific synthetic route of the generated targeted compounds is shown in Scheme . The method used was adopted from previous reports. , Briefly, citral was used as the raw material and converted into citronellal through a Pd/TPP hydrogenation reaction. Then, the obtained citronellal was oxidized to citronellic acid (compound b ) by the oxidation reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The specific synthetic route of the generated targeted compounds is shown in Scheme . The method used was adopted from previous reports. , Briefly, citral was used as the raw material and converted into citronellal through a Pd/TPP hydrogenation reaction. Then, the obtained citronellal was oxidized to citronellic acid (compound b ) by the oxidation reaction.…”
Section: Methodsmentioning
confidence: 99%
“…In the production of citronellic acid, it has been found that 1 wt% Au/TiO 2 and 1 wt% Au/Al 2 O 3 , made using the DP urea method gave conversions of 97% and 100% (as determined by GC) in aqueous conditions using oxygen at 80°C and pH 9 at atmospheric pressure [11]. Au particle Continuous conversion of glucose to gluconic acid over 110 days using 0.3% Au/Al 2 O 3 , at different retention times and resulting average conversions, adapted from ref.…”
Section: Selective Oxidation In the Liquid Phasementioning
confidence: 99%
“…One of the most important products is citronellal (Figure ), which can be used as a key compound in organic synthesis. It can be used as a key intermediate or chiral source in the total synthesis of natural and non-natural compounds such as pheromones and cyclic, polycyclic, and alycyclic compounds. It can also be used as a raw material for fine commodities in the food, fragrance, cosmetic, and pharmaceutical industries. …”
Section: Introductionmentioning
confidence: 99%